Restoration of the Activated Rig-I Pathway in Hepatitis C Virus (HCV) Replicon Cells by HCV Protease, Polymerase, and NS5A Inhibitors In Vitro at Clinically Relevant Concentrations - Kalkeri, Gururaj (American Society for Microbiology, 2013)
Development of persistent hepatitis C virus (HCV) infection may be mediated by HCV NS3 · 4A protease-dependent inhibition of host innate immunity. When double-stranded RNA (dsRNA) is detected in virus-infected cells, host innate immunity mounts an antiviral response by upregulating production of type I interferons (α/β interferon [IFN-α/β]); HCV counters by cleaving the IFN-β stimulator 1 (IPS-1) adaptor protein, decreasing synthesis of IFN-α/β. We evaluated HCV protease (telaprevir, boceprevir, and TMC435350), polymerase (HCV-796 and VX-222), and NS5A (BMS-790052) inhibitors for the ability to restore IPS-1-mediated Rig-I signaling by measuring Sendai virus-induced IFN-β promoter activation in HCV replicon cells after various exposure durations. All direct-acting HCV antivirals tested restored mitochondrial localization of IPS-1 and rescued Sendai virus-induced IRF3 signaling after 7 days by inhibiting HCV replication, thereby reducing the abundance of HCV NS3 · 4A protease. With 4-day treatment, HCV protease inhibitors, but not polymerase inhibitors, restored mitochondrial localization of IPS-1 and rescued IFN-β promoter activation in the presence of equivalent levels of NS3 protein in protease or polymerase inhibitor-treated cells. The concentrations of HCV protease and polymerase inhibitors needed to rescue IRF3-mediated signaling in vitro were in the range of those observed in vivo in the plasma of treated HCV patients. These findings suggest that (i) HCV protease, polymerase, and NS5A inhibitors can restore virus-induced IRF3 signaling by inhibiting viral replication, thereby reducing NS3 protease levels, and (ii) HCV protease inhibitors can restore innate immunity by directly inhibiting NS3 protease-mediated cleavage of IPS-1 at clinically achievable concentrations.